Open access: a revolution in scientific publishing - Kataria, Bhaven C. (International Journal of Advances in Medicine, 2017)
The way that research is communicated is changing rapidly. The internet has made it possible, a revolutionary way of providing access to the articles published in scholarly journals. The rising cost of subscription of scholarly journals, has seriously hampered the ability of libraries, research centers, and researchers to acquire publications necessary for research and knowledge enhancement. Open access publishing provides a way for addressing this challenge by offering a very cost-effective alternative to the traditional publishing model. Before the mid-1990s, most of the journals were available only on paper and accessible by subscription. By the end of the 20th century, most journals had moved their content to online platforms.Open access (OA) in simple meaning refers to unrestricted online access to the articles published in scholarly journals. There are two distinct ways articulated in the Budapest Open Access Initiative: (1) Articles directly provided by the journal publisher (also called “gold OA”), or (2) Indirectly by author self-archiving and/or being uploaded and made freely available somewhere else on the web (also called “green OA”). Green open access requires the author to deposit a peer-reviewed manuscript in an institutional or central repository such as PubMed Central. Both options increase the potential readership of any article.